Makna Filosofis dan Saintifik Terkait Tauhid (Keesaan Tuhan) - Amaliyah, Nur; Musawamah, Aprilia; Usnia; Ummah, Iin Inayatul; Rosa, Andi; Muhsin, Masyrukin (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This research examines the philosophical and scientific meaning related to tawhid (oneness of God) in Islam through qualitative research methods with a literature study approach. The research aims to understand the concept of monotheism from ontological, epistemological and axiological dimensions. The results show that monotheism is not just a recognition of the oneness of Allah, but is a basis for understanding the reality of life. Ontologically, tawhid affirms Allah as Absolute Being. In epistemology, monotheism bridges revealed knowledge and reason. Meanwhile, in axiology, monotheism provides a system of values ​​and ethics that form character. This concept is supported by modern scientific discoveries such as the Big Bang theory, DNA and quantum entanglement. In practice, monotheism gives birth to the principles of anti-discrimination, human unity, and the concept of the caliph who protects the environment. In the modern era, monotheism remains relevant as a dynamic concept that provides solutions to contemporary problems, while maintaining the essence of recognizing the oneness of Allah.